Are plasma cell-rich inflammatory conditions of the oral mucosa manifestations of IgG4-related disease?. Issue 10 (8th June 2015) - Cottom, Hannah; Mighell, Alan J; High, Alec; Bateman, Adrian C
Abstract : Aim: The aim of this study was to characterise plasma cell infiltrates, in terms of IgG4 positivity, in specific and non-specific plasma cell-rich chronic inflammatory conditions of the oral mucosa. Exploring the possibility that specific plasma cell-rich oral inflammatory conditions have association with or represent an oral manifestation of immunoglobulin G4-related disease (IgG4-RD). Methods: Ten patients with plasma cell-rich chronic inflammatory conditions of the oral mucosa were identified (seven—plasma cell mucositis and three—non-specific diffuse oral mucosal inflammation with ulceration). For each patient, the clinical record and H&E-stained sections were reviewed. Immunohistochemistry for IgG and IgG4 antibodies was performed on sections from the corresponding paraffin block, permitting calculation of the mean number of IgG4+ plasma cells per high-power field (HPF) and the IgG4+/IgG+ plasma cell ratio. Results: In all the cases, only one histological hallmark of IgG4-RD—a dense lymphoplasmacytic infiltrate—was seen. Review of the medical histories did not reveal any features representing other manifestations of IgG4-RD. The number of IgG4+ plasma cells exceeded 100 per HPF in half of the cases. Only two cases had an IgG4+/IgG+ plasma cell ratio of >40%; both of which were in the non-specific oral inflammatory group. Conclusions: Our study suggests that plasma cell mucositis does not meet microscopic criteria for IgG4-RD. It importantly reinforces the opinion that IgG4+ plasma cells are major components of chronic inflammation in the oral cavity and the pertinence of correct contextual interpretation of histopathological features with clinical findings.